William and Mabel Meed in front of their log cabin at lower end of Lake Laberge, Yukon Territory, spring 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.250 Log cabin at lower Lake Laberge (1902) where Mr. & Mrs. Meed stayed while "Prospector" was in winter quarters being re-fitted and having superstructure built. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number